Kemampuan Menulis Teks Prosedur Siswa Kelas VII-1 SMP Yas’A Sumenep - Olivia Ananda; Abelia Nur Hikmah; Fatimiyah Ratu Izzahroh; Aisyah Aisyah; Abdul Wahab (Kampus Akademik Publiser, 2026)
This study aims to determine the writing ability of procedural texts of class VII-1 students of Yas'a Junior High School, Sumenep. This study uses a quantitative approach with a descriptive research type. The research subjects were 10 students. The data collection technique was carried out through a procedural text writing test with the theme